Dose-response Protective Effect of Salbutamol on Methacholine Airway Responsiveness using Pressurized Metered Dose Inhalers and Turbuhalers. Issue 2 (3rd April 1998) - Wong, Albert G; O'Byrne, Paul M; Lindbladh, Christer; Inman, Mark D; Ståhl, Elisabeth; Hargreave, Frederick E
Abstract : The purpose of this study was to estimate the relative dose potency of salbutamol Turbuhaler compared with salbutamol pressurized metered dose inhaler (pMDI) with respect to the protective effect against methacholine bronchoconstriction. Twenty-three asthmatic subjects with stable asthma participated in the study. Baseline forced expiratory volume in 1 s (FEV1 ) was 70% or more of predicted, and baseline methacholine provocative concentration causing a 20% fall in FEV1 (PC20 ) was 4 mg/mL or less. The design was randomized, double-blind, double-dummy, crossover and placebo controlled and was conducted over seven study days. On each study day, the subjects inhaled 50 µg or 100 µg of salbutamol via Turbuhaler, 100 µg, 200 µg, 400 µg or 800 µg of salbutamol via pMDI, or placebo in randomized order. PC20 was determined 30 mins after inhalation. Increasing doses of salbutamol pMDI increased the PC20 in a dose-dependent fashion from 3.9 mg/mL after placebo to 13.3 mg/mL after pMDI 100 µg, 19.0 mg/mL after 200 µg, 32.6 mg/mL after 400 µg, and 35.1 mg/mL after 800 µg. The half-maximum response dose for pMDI (ED50 ) was 104 µg. Salbutamol Turbuhaler 50 µg increased the PC20 to 10.0 mg/mL and 100 µg to 12.6 mg/mL. Salbutamol pMDI 200 µg provided significantly greater protection to methacholine than pMDI 100 µg or Turbuhaler 100 µg and significantly less protection than pMDI 400 µg (P<0.05). This study demonstrates that the relative protective dose potency of inhaled beta-agonists can be determined by comparing their effects on methacholine airway responsiveness. The estimated relative protective dose potency for salbutamol Turbuhaler in comparison with pMDI was 1.38 (95% CI 0.67 to 2.87) at 50 µg and was 0.96 (95% CI 0.56 to 1.64) at 100 µg.